2021
DOI: 10.1186/s12943-021-01355-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXCR2 inhibits the progression of lung cancer and promotes therapeutic effect of cisplatin

Abstract: Background Drug-resistance and severe side effects of chemotherapeutic agents result in unsatisfied survival of patients with lung cancer. CXCLs/CXCR2 axis plays an important role in progression of cancer including lung cancer. However, the specific anti-cancer mechanism of targeting CXCR2 remains unclear. Methods Immunohistochemical analysis of CXCR2 was performed on the microarray of tumor tissues of clinical lung adenocarcinoma and lung squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 67 publications
3
72
0
Order By: Relevance
“…CXCR2 deletion has led to decreased metastasis and improved response to paclitaxel in a mouse model of breast cancer [167]. In a melanoma model, the CXCR2 inhibitor Navarixin synergised with mitogen-activated protein kinase inhibition [117] whereas the inhibitor SB225002 improved the antiangiogenic therapy Sorafenib in an ovarian tumor model [118] and enhanced the therapeutic effect of cisplatin via the regulation of neutrophils' infiltration in a lung cancer model [119]. The CXCR1 and CXCR2 inhibitor Reparixin was also able to improve tumor cell apoptosis and decrease tumor volume in a gastric cancer model, when in combination with 5-fluorouracil [120].…”
Section: Cxcr2mentioning
confidence: 99%
“…CXCR2 deletion has led to decreased metastasis and improved response to paclitaxel in a mouse model of breast cancer [167]. In a melanoma model, the CXCR2 inhibitor Navarixin synergised with mitogen-activated protein kinase inhibition [117] whereas the inhibitor SB225002 improved the antiangiogenic therapy Sorafenib in an ovarian tumor model [118] and enhanced the therapeutic effect of cisplatin via the regulation of neutrophils' infiltration in a lung cancer model [119]. The CXCR1 and CXCR2 inhibitor Reparixin was also able to improve tumor cell apoptosis and decrease tumor volume in a gastric cancer model, when in combination with 5-fluorouracil [120].…”
Section: Cxcr2mentioning
confidence: 99%
“…TANs have pro-tumor activity by producing immunosuppressive soluble mediators such as TGF-β and arginase [ 194 , 195 ]. Similar to normal neutrophils, TANs utilize the CXCR2 axis for their recruitment [ 196 ]. In addition, TAMs, monocytic-MDSCs, polymorphonuclear-MDSCs, and TANs can produce the CCR4 ligands CCL17 and CCL22 in tumor tissues, contributing to tumor progression by recruiting CCR4-expressing Treg cells [ 3 ].…”
Section: Tam Mdsc and Tanmentioning
confidence: 99%
“…CXCR2 has been shown to play a major role in tumor progression by recruiting polymorphonuclear type MDSCs and TANs into the tumor microenvironment in murine models of cancers such as colon cancer, pancreatic cancer, head and neck cancer, and melanoma [ 196 , 224 , 225 , 226 ]. A recent study has shown that inhibition of CXCR2 using SB225002, a CXCR2 inhibitor, significantly decreases infiltration of TANs in tumor tissues and suppresses tumor growth in a murine lung cancer model [ 196 ]. However, CXCR2 is a major trafficking receptor for neutrophils and thus blocking CXCR2 may increase susceptibility to bacterial infection.…”
Section: The Chemokine Superfamily As Therapeutic Targets In Cancer Immunotherapymentioning
confidence: 99%
“…Several potential therapeutic strategies aim to inhibit MDSC differentiation, migration, and recruitment via the blocking of C-X-C Motif Chemokine Receptor 1 (CXCR1) which has a key role in pre-metastatic formation [33,34], with CXCR2 directing the migration of the MDSC to the tumor [35]. However, CXCR2 serves an essential role in the chemoresistance of different types of tumors, including breast and lung cancer [36,37]. Therefore, a recent study aimed to target CXCR2 by IFN-γ improved clinical outcomes and proven the effectiveness of anti-PD1 therapy in pancreatic cancer [38].…”
Section: Myeloid-derived Suppressor Cells (Mdscs)mentioning
confidence: 99%